Collect More, Spend Better : Public Investment in Asian Frontier Markets - Ghazanchyan, Manuk; Douglass, Kaitlyn; Jonas, Jiri.; Marto, Ricardo (Washington, D.C. : International Monetary Fund, 2017)
We use a dynamic small open economy model to explore the macroeconomic impact of alternative public investment scaling-up scenarios, analyzing how improving the efficiency of capital spending and of tax revenue collection affect growth and debt sustainability for three fast-growing Southeast Asian economies: Cambodia, Sri Lanka, and Vietnam. We show that a gradual public investment profile is more favorable than front-loading capital spending because we assume governments are able to gradually learn how to invest more efficiently, accelerating public capital accumulation and therefore growth. We discuss the pros and cons of alternative financing options and identify the financing mix that generates the best macroeconomic outcome. Sometimes overlooked, improving the efficiency of revenue collection over time may ease the burden of fiscal adjustment, achieving higher GDP growth with substantially lower debt-to-GDP ratios, and will help policymakers efficiently meet the challenge of addressing large infrastructure gaps while maintaining debt sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet